Bile duct surgery in the treatment of hepatobiliary and gallbladder malignancies: effects of hepatic and vascular resection on outcomes. Issue 12 (December 2015) - Shen, Perry; Fino, Nora; Levine, Edward A.; Eversole, Pamela; Clark, Clancy
Abstract: Background: Resection of the bile duct is required for the treatment of cholangiocarcinoma and is sometimes indicated in resections of liver and gallbladder malignancies. The goal of this retrospective review was to characterize surgical outcomes in patients submitted to bile duct resection for malignancy when additional procedures, specifically hepatic or vascular resections, were performed. Methods: The American College of Surgeons National Surgical Quality Improvement Program database was searched to identify a total of 747 patients who underwent: (i) biliary‐enteric anastomosis (BEA) only (Group 1, n = 266); (ii) BEA with hepatic resection (Group 2, n = 439), or (iii) BEA with hepatic and vascular resection (Group 3, n  = 42). Postoperative outcomes were compared and regression‐adjusted risk factors were analysed to produce observed and expected (O/E) morbidity and mortality ratios. Results: The performance of hepatic and vascular resections significantly increased rates of overall morbidity ( P  < 0.001) and mortality ( P  = 0.021). Risk‐adjusted O/E mortality ratios in Groups 1, 2 and 3 were 1.44 [95% confidence interval (CI) 0.84–2.30], 2.16 (95% CI 1.51–2.98) and 5.92 (95% CI 2.54–11.66), respectively. Multivariate analysis identified Group 2 ( P  < 0.001) and Group 3 ( P = 0.001) status as independent predictors of morbidity, and Group 3 status ( P = 0.008) as independently associated with mortality. More than 30% of deaths were associated with pulmonary complications and septic shock. Conclusions: The addition of hepatic and vascular resections to bile duct resection significantly increased morbidity and mortality. The high O/E mortality ratios for patients in Groups 2 and 3 suggest these outcomes can be improved.